2017
DOI: 10.3389/fpls.2017.00116
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sources of Witchweed (Striga) Resistance from Wild Sorghum Accessions

Abstract: Sorghum is a major food staple in sub-Saharan Africa (SSA), but its production is constrained by the parasitic plant Striga that attaches to the roots of many cereals crops and causes severe stunting and loss of yield. Away from cultivated farmland, wild sorghum accessions grow as weedy plants and have shown remarkable immunity to Striga. We sought to determine the extent of the resistance to Striga in wild sorghum plants. Our screening strategy involved controlled laboratory assays of rhizotrons, where we art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 40 publications
8
69
0
Order By: Relevance
“…Such specificity may be related to differences in quality, identity and/or quantity of the haustorium factor. The observed differential response is consistent with a previous report by Mbuvi et al (2017) who reported that the potential number of haustoria is a product of the concentration and/or quality of haustoria inducing factor and the parasite's individual ability to respond. The host specificity and variability of S. hermonthica populations might affect the efficiency of introducing new resistant cultivars as a control measure against the parasitic weed.…”
Section: Effects Of In-situ Root Exudates Of Sorghum Cultivars On Pensupporting
confidence: 92%
“…Such specificity may be related to differences in quality, identity and/or quantity of the haustorium factor. The observed differential response is consistent with a previous report by Mbuvi et al (2017) who reported that the potential number of haustoria is a product of the concentration and/or quality of haustoria inducing factor and the parasite's individual ability to respond. The host specificity and variability of S. hermonthica populations might affect the efficiency of introducing new resistant cultivars as a control measure against the parasitic weed.…”
Section: Effects Of In-situ Root Exudates Of Sorghum Cultivars On Pensupporting
confidence: 92%
“…Our ndings underscore the need to continuously screen hosts for Striga resistance as a rmed by successful identi cation of new Striga resistant sorghum genotypes. The resistance by the genotypes, as determined by the number, size and biomass of Striga seedlings attached, is comparable to what has been reported in previous work that used rhizotrons [12,17]. For example, we found an average of 57 attachments on N13 compared to a mean of 56 reported by [12] and 75 [18].…”
Section: New Sources Of Striga Resistance From the Sorghum Diversity supporting
confidence: 89%
“…5). The differential response in N13 could possibly be attributed to mechanical resistance, as reported by Grenier et al (2007) and Mbuvi et al (2017). In addition, high proportions of sorgomol in some genotypes, such as Wad Fahel, did not necessarily result in higher germination-stimulating activity, although it was associated with a higher Striga infection level in the pot experiment (Fig.…”
Section: Discussionmentioning
confidence: 65%